2008
DOI: 10.3748/wjg.14.1456
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine midgut volvulus without malrotation: Diagnosis from the ‘coffee bean sign’

Abstract: Fetal midgut volvulus is quite rare, and most cases are associated with abnormalities of intestinal rotation or fixation. We report a case of midgut volvulus without malrotation, associated with a meconium pellet, during the gestation period. This 2.79 kg, 33-wk infant was born via a spontaneous vaginal delivery caused by preterm labor. Prenatal ultrasound showed dilated bowel loops with the appearance of a 'coffee bean sign'. This patient had an unusual presentation with a distended abdomen showing skin disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 13 publications
1
55
0
4
Order By: Relevance
“…This is a segmental dilatation of a bowel loop which resembles a whirl in water. Another characteristic sign of volvulus is a 'coffee bean sign' which is a dilatation of a very short segment of bowel which resembles a coffee bean [7] . Other findings suggestive of congenital volvulus on prenatal ultrasound are: intestinal dilatation, polyhydramnios, intraperitoneal calcification, ascites and fetal hydrops [1,[7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a segmental dilatation of a bowel loop which resembles a whirl in water. Another characteristic sign of volvulus is a 'coffee bean sign' which is a dilatation of a very short segment of bowel which resembles a coffee bean [7] . Other findings suggestive of congenital volvulus on prenatal ultrasound are: intestinal dilatation, polyhydramnios, intraperitoneal calcification, ascites and fetal hydrops [1,[7][8][9] .…”
Section: Discussionmentioning
confidence: 99%
“…Another characteristic sign of volvulus is a 'coffee bean sign' which is a dilatation of a very short segment of bowel which resembles a coffee bean [7] . Other findings suggestive of congenital volvulus on prenatal ultrasound are: intestinal dilatation, polyhydramnios, intraperitoneal calcification, ascites and fetal hydrops [1,[7][8][9] . Intestinal dilatation and polyhydramnios in congenital volvulus have been described by Molvarec et al [1] , Jequier et al [8] and Has and Gunay [6] .…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort study, 4 volvulus cases were detected antenatally and confirmed at birth, of whom 3 died after birth. Prenatal sonographic findings such as dilated bowel loops, the ‘whirlpool sign' (twisting of bowel loops around the mesenteric artery) and the ‘coffee bean sign' (distention of a very short segment of bowel which resembles a coffee bean) are compatibles for intestinal volvulus [43,44] (fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, non-specific features, such as distended bowel loops, ascitis or hydramnios with normal position of mesenteric vessels were described on fetal ultrasound scans or MRI. In few studies the diagnosis of volvulus without malrotation was advanced when ultrasound scan revealed a long segment of bowel loops which formed a mass with a typical whirlpool or snail configuration, whereas others reported the ‘coffee bean sign’ 3 8 9. Like in our cases, some authors had reported that the appearance of a curved anechoic mass was a suggestive sign of segmental volvulus 3 8…”
Section: Discussionmentioning
confidence: 51%